Sistem Pengurusan Dokumen Asrama dan Fail Kolej Vokasional Tanjung Puteri (KVTP) - MOHAMMAD FAROS, AMIRA ERDYNA; Firkhan Ali Hamid Ali (Applied Information Technology And Computer Science, 2024)
At Kolej Vokasional Tanjung Puteri (KVTP), office workers are responsible for managing file records and letters, while the dormitory supervisors handle document recording. Manual processes for student data and letter records have led to data duplication and inaccuracies. Unsystematic file storage complicates the search. The main purpose development of this system is to focus on providing a database that allows them to keep records of files and documents as needed. The developed system is Web-based and applies the Waterfall Model software development methodology. The development tools used are Visual Studio Code, XAMPP, as well as MySQL as a database. The proposed system can store all records of files and documents in a database with enhanced features. It is hoped that this system can help users to manage files or documents more efficiently. This system is expected to provide the smartphone version so that users can easily access it.